Monitoring anthropometry and fitness using maturity groups within youth rugby league - Till, K.; Jones, B. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to evaluate the anthropometry and fitness, and change in these characteristics over time, of youth rugby league players by using maturity status to determine annual categories instead of traditional chronological annual-age grouping. One hundred and twenty-one male rugby league players were assessed using anthropometric (i.e., height, sitting height, body mass, and sum of 4 skinfolds) and fitness (i.e., vertical jump, medicine ball chest throw, 10- and 20-m sprint, and multistage fitness test [MSFT]) measures over a 5-year period. Each player was classified into 1 of 6 maturity groups based on their maturity offset (years from peak height velocity, i.e., 1.5 YPHV). Multivariate analysis of variance analyses identified significant (p < 0.001) main effects for maturity group for cross-sectional characteristics and longitudinal change in performance over time. Analyses demonstrated that more mature groups had greater anthropometric and fitness characteristics, except for endurance performance (MSFT: -2.5 YPHV = 1,872 ± 18 m vs. 2.5 YPHV = 1,675 ± 275 m). For longitudinal changes in characteristics over time, a significant effect was only identified for height and sitting height (p = 0.05). These findings provide comparative data for anthropometric and fitness characteristics and change in performance over time in accordance with the maturity status within youth rugby league players. Classifying players into annual maturity groups may be an additional or alternative assessment method for evaluating anthropometry and fitness performance in adolescent populations. Furthermore, tracking performance changes over time, especially in relation to maturation, may reduce the limitations associated with chronological annual-age grouping.